As garotas (des)amélias : acolhimento institucional e sexualidade - Gonçalves, Bruna Vasconcelos (2014)
This research presents a study regarding the institucionalised practices that covers the topics of sexuality in a children and youth´s shelter located in Aracaju. In order to develop the research, are used reports of the experiences that took place on the mentioned institute. This reports give life to the (Des)Amélias girls. Listing this experiences as problematization possibilities of practices that envolved the researched shelter and beyond it, this research investigate the following aspects: the relation between youth sexuality and youth protection policies; the institutional shelter through sexual repression actualization; sexuality as a tool for the analysis of the institutional shelter; the existence of other relations, besides the ones mentioned, with sexuality and the practices experienced by the ones led into children and youth´s shelter. In pursuance of the mentioned research problems, it was necessay to take a look in readings regarding public policies based on children and teenagers, from authors that traces the social history of youth in Brazil. It was also taken into consideration the histoty of sexuality, the course of psychology, psychoanalysis, psychiatry and sexuality, as well as the concepts of gender, sexual repression, ethics, moral, judicialization and institutionalization of sexuality.